14, 15β-dihydroxyklaineanone inhibits HepG2 cell proliferation and migration through p38MAPK pathway. (17th May 2020) - Pei, Xiao-Dong; He, Song-Qing; Shen, Li-Qun; Wei, Jing-Chen; Li, Xue-Sheng; Wei, Yan-Yan; Zhang, Yu-Meng; Wang, Xin-Yu; Lin, Feng; He, Zhi-Long; Jiang, Li-He
Abstract: Objectives: Eurycoma longifolia Jack ( Simaroubaceae ) is commonly distributed in the Southeast Asia and Indo China, which has been shown to possess antianxiety, antibacterial, anticancer, antifungal, anti-inflammatory, antimalarial and antioxidant biological activities. 14, 15β-dihydroxyklaineanone is a diterpene isolated from E. longifolia Jack, which is cytotoxic against human lung cancer and human breast cancer cell lines. However, the effects and underlying mechanisms of 14, 15β-dihydroxyklaineanone on hepatocellular carcinoma remain unknown. Methods: Cell viability assay and colony formation assay were used to measure HepG2 cell proliferation. Flow cytometry was used to analyse cell cycle and apoptosis. Wound-healing assay and transwell assay were used to observe cells migration. RNA sequencing and the enrichment of differentially expressed genes (DEGs) in Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were used to find and determine underlying pathways. Key findings: We found that 14, 15β-dihydroxyklaineanone inhibited the growth and migration of HepG2 cells but did not induce cell apoptosis. 14, 15β-dihydroxyklaineanone induced S cell cycle arrest by downregulating the expression levels of cyclin A, p-CDK2, cyclin B1, p21, E2F-1 and PCNA. In addition, RNA sequencing showed that 14, 15β-dihydroxyklaineanone regulated MAPK pathway by increasing the expression levels of phosphor-p38. Downregulating of p38 via both p38 inhibitor (SB203580) and p38-siRNA could antagonize the inhibition of cell proliferation and migration and reverse the changes in p-p38, E-cadherin, N-cadherin and PCNA expression induced by 14, 15β-dihydroxyklaineanone treatment. Conclusions: 14, 15β-dihydroxyklaineanone inhibited cell proliferation and migration through regulating p38 MAPK pathway in HCC cells.